Perbaikan Kualitas Layanan TK Telkom Buah Batu Dengan Integrasi SERVQUAL, KANO Dan SWOT - Rinjani, Kiki; Nurhayati, Ai; Fauziyah, Rahma (CORISINDO 2025, 2025)
PAUD a strategic role in shaping children’s character and learning abilities from an early age. The growing interest of parents in early education requires schools to improve service quality in order to meet expectations and maintain competitiveness. This study aims to evaluate the service quality of TK Telkom Buah Batu using the Servqual and Kano methods. The Servqual analysis results show a service quality value (Q) of 0.849, indicating that the service has not yet met the “good” category. The Kano analysis identifies 15 attributes in the One dimensional category (T1, T2, T4, RL1–RL5, RV1, RV2, A1–A3, E1, E3) that must be prioritized for improvement, as well as two attributes in the Attractive category (T3 and E2), which, although not a priority, can still enhance parental satisfaction if improved. This study contributes by providing relevant managerial strategies to improve service quality, parental satisfaction, and the competitiveness of TK Telkom Buah Batu amidst the competition among PAUD schools in Lengkong.